(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Biblionline Vol. 9, n. 2 (2013) Link de acesso ao número http://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1354/showToc